2011
DOI: 10.1128/aac.01362-10
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Early Step of the Futalosine Pathway

Abstract: We recently demonstrated that the futalosine pathway was operating in some bacteria for the biosynthesis of menaquinone and that futalosine was converted into dehypoxanthinyl futalosine (DHFL) by an MqnB of Thermus thermophilus. In this study, we found that aminodeoxyfutalosine, which has adenine instead of hypoxanthine in futalosine, was directly converted into DHFL by an MqnB of Helicobacter pylori. Therefore, this step is potentially an attractive target for the development of specific anti-H. pylori drugs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 6 publications
(5 reference statements)
2
51
0
Order By: Relevance
“…This situation was at odds with the fact that MKs had been extensively used as chemotaxons in Streptomyces and related organisms (Collins et al 1985). Again, a convergent pathway was first inferred from the GSMRs of S. coelicolor (Borodina et al 2005) and this discrepancy was experimentally solved by the discovery of a completely novel MK biosynthetic pathway Seto et al 2008;Arakawa et al 2011) that starts from futalosine or aminodeoxyfutalosine (mqn genes; Fig. 2).…”
Section: Evolutionary Implications Of Gsmrsmentioning
confidence: 94%
“…This situation was at odds with the fact that MKs had been extensively used as chemotaxons in Streptomyces and related organisms (Collins et al 1985). Again, a convergent pathway was first inferred from the GSMRs of S. coelicolor (Borodina et al 2005) and this discrepancy was experimentally solved by the discovery of a completely novel MK biosynthetic pathway Seto et al 2008;Arakawa et al 2011) that starts from futalosine or aminodeoxyfutalosine (mqn genes; Fig. 2).…”
Section: Evolutionary Implications Of Gsmrsmentioning
confidence: 94%
“…4 In this study, we added 12.5, 25, 50, and 100 mg ml −1 of MK taking account of probable difference of uptake and utilization efficiency between the two strains. As shown in Figure S8, the growth inhibition of B. halodurans C-125 by compound 1 was clearly recovered 6 by adding MK in a concentration-dependent manner, and minimal effective concentration of MK was 0.05 mg ml −1 . These results suggested that tirandamycins 1 and 2 were specific inhibitors of the futalosine pathway in B. halodurans C-125.…”
Section: Figure 2 Structures Of the Tirandamycinsmentioning
confidence: 92%
“…In Escherichia coli, MK was shown to derive from chorismate via a pathway involving eight enzymes, designated MenA-H (Figure 1a, canonical pathway). 1, 2 However, we revealed that an alternative pathway (Figure 1b, futalosine pathway) [3][4][5][6][7] was operating in some microorganisms including Helicobacter pylori, which causes gastric carcinoma. As humans and some useful intestinal bacteria, such as lactobacilli, possess the classical pathway, and MK biosynthesis is essential for the survival of microorganisms, the futalosine pathway is an attractive target for the development of specific anti-H. pylori drugs.…”
mentioning
confidence: 97%
“…The striking feature that makes lysocin E unique from other known antibiotics is its potent bactericidal (18,19) that involves conversion of chorismate into 6-amino-6-deoxyfutalosine by MqnA and MqnE. Another important step of the alternative pathway, conversion of 6-amino-6-deoxyfutalosine to dehypoxanthine futalosine (DHF), occurs by either a single step reaction catalyzed by methylthioadenosine nucleosidase (MTAN) as in H. pylori and C. jejuni or a two-step reaction catalyzed by 6-amino-6-deoxyfutalosine deaminase (20,21) and MqnB as in S. coelicolor and T. thermophilus (18) (Figure 4). The enzymatic reaction to convert DHF to MK involves MqnC, MqnD and possibly MenA and MenG (22).…”
Section: Antibiotics Interacting Directly With Mkmentioning
confidence: 99%